Analisis Perbedaan Minat Baca Sejarah Indonesia Siswa IPA dan IPS Kelas XI SMA Negeri 1 Kubung - Latifa Putri; Wahidul Basri (Jurusan Sejarah FIS UNP, 2021)
The research is motivated because is that there are differences in interest in reading Indonesian history between students of class XI science and class XI social studies at SMA Negeri 1 Kubung. The purpose of this study was to analyze the differences in reading interest in Indonesian history for science and social studies students in class XI of SMA Negeri 1 Kubung. This research is a quantitative research using the Expost Facto research method with a comparative study type. The results of this study indicate that there is a significant difference between the interest in reading Indonesian history of science and social studies students in class XI SMA Negeri 1 Kubung. This can be evidenced from the results of data processing which shows that interest in reading Indonesian history in class XI science is generally in the low category with a percentage of 33%, while interest in reading Indonesian history in class XI social studies is generally in the medium category with a percentage of 27%. It can be concluded that the interest in reading Indonesian history in class XI science is lower than reading interest in Indonesian history in class XI social studies. Keyword: Reading Interest, Indonesian History